Learning management system implementation: a case study in the Kyrgyz Republic. Issue 8 (17th November 2018) - Nurakun Kyzy, Zhumagul; Ismailova, Rita; Dündar, Hakan
ABSTRACT: In this paper, the determinants of the intention to use online learning management system (LMS) among students in one of universities in the Kyrgyz Republic were studied, using quantitative and qualitative analysis. A total of 541 responses from students, enrolled in online courses during the fall and spring semesters 2016–2017, were used to examine students attitude toward online education. In addition, interviews with six instructors were conducted. Results showed that success of students in e-courses depend on year of education and the academic major of students. Factors, defined in the scope of this work, namely, technical characteristics of LMS, ease of use, feedback options of LMS and advantages of LMS use, were also found to be significant for students in their success in online courses. In interviews with instructors, three main points were highlighted, namely, problem with students' perception of online courses, lack of online education experience among instructors and administrative issues.